Filantropi Islam dan Regulasi Hukum Positif: Kajian Fikih Sosial terhadap Program Donasi Dana Dompet Dhuafa Sulawesi Selatan - Wildan, Muhammad; Asni, Asni; Sanusi, Nur Taufiq (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the practice of cutting social fund donations by the Dompet Dhuafa Philanthropic Institute of South Sulawesi from the perspective of social fiqh and positive law. The focus of this research includes the mechanisms of fund management by philanthropic institutions, as well as how these practices are normatively reviewed in the context of Islamic law and national regulations. This study uses a qualitative approach with a field study method. Data was collected through observation, in-depth interviews, and documentation, which was then strengthened by literature studies of laws and regulations, scientific literature, and information from the official websites of related institutions. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that Dompet Dhuafa South Sulawesi collects funds from ZISWAF and Corporate Social Responsibility (CSR) sources, with an allocation of 12.5% for operational needs and amil rights. From the perspective of social fiqh, the deduction is justified based on the provisions in QS. At-Taubah verse 60 and MUI Fatwa No. 8 of 2011, which stipulates the share of amil at 12.5%, in line with the views of scholars such as KH. Sahal Mahfudh and KH. Ali Yafie who emphasized the importance of optimizing zakat institutions in community empowerment in accordance with the principles of maqāṣid al-syarīʿah. Meanwhile, in the context of positive law, the deduction of social funds by Islamic philanthropic institutions is regulated in Article 67 paragraph (2) of Government Regulation No. 14 of 2014 as a derivative of Law No. 23 of 2011, and strengthened by the Decree of the Ministry of Religion No. 733 of 2018 and BAZNAS Regulation No. 1 of 2016, which allows deductions of up to 20% outside of zakat funds. On the other hand, public philanthropic institutions or Money and Goods Collection Institutions (PUB) are subject to Government Regulation No. 29 of 1980 and Permensos No. 8 of 2021, which limit operational costs to a maximum of 10% without specific regulations regarding the salary of administrators. This research emphasizes the need for regulatory distinction between Islamic and public philanthropic institutions, as well as the strengthening of transparency in the management of social funds to maintain public trust and the effectiveness of aid distribution.